1992
DOI: 10.1128/aem.58.4.1266-1270.1992
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Molecular Size Distribution of Cellulose during Attack by White Rot and Brown Rot Fungi

Abstract: The kinetics of cotton cellulose depolymerization by the brown rot fungus Postia placenta and the white rot fungus Phanerochaete chrysosporium were investigated with solid-state cultures. The degree of polymerization (DP; the average number of glucosyl residues per cellulose molecule) of cellulose removed from soil-block cultures during degradation by P. placenta was first determined viscosimetrically. Changes in molecular size distribution of cellulose attacked by either fungus were then determined by size ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(38 citation statements)
references
References 12 publications
3
33
0
Order By: Relevance
“…The early observations of Puls and Wood (129) have been further elaborated by other authors who have demonstrated that the in vivo mechanism of cellulose degradation differs fundamentally among wood-degrading fungi and, consequently, results in different modes of decay (78). These and other authors (79,159) have also shown that recombinant cellulase monocompents (both endoglucanases and cellobiohydrolases) effectively reduce the DP of different purified cellulose substrates by various mechanisms (79,159), suggesting that depolymerization was largely a function of the nature of the cellulosic substrate being attacked.…”
Section: Substrate Factors Limiting Hydrolysismentioning
confidence: 87%
“…The early observations of Puls and Wood (129) have been further elaborated by other authors who have demonstrated that the in vivo mechanism of cellulose degradation differs fundamentally among wood-degrading fungi and, consequently, results in different modes of decay (78). These and other authors (79,159) have also shown that recombinant cellulase monocompents (both endoglucanases and cellobiohydrolases) effectively reduce the DP of different purified cellulose substrates by various mechanisms (79,159), suggesting that depolymerization was largely a function of the nature of the cellulosic substrate being attacked.…”
Section: Substrate Factors Limiting Hydrolysismentioning
confidence: 87%
“…During TFA hydrolysis amorphous (noncrystalline) cellulose is degraded, and constituents of the walls of microbial cells are hydrolysed, releasing a suite of hexose and pentoses. This hydrolysis is mimicked by the brown-rot fungi in their ability to differentiate between amorphous and crystalline cellulose (Kleman-Leyer et al, 1992). The larger concentration of carbohydrate-C extracted by TFA in the grassland and ash profiles compared with the spruce profile suggests a difference in litter quality, rate and extent of decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the recovered cellulose by viscosimetry and by GPC after derivatization showed that both G. trabeum and P. placenta were clearly cellulolytic in these cultures ( Table 1). The depolymerization rates were somewhat slower than the rate reported earlier for P. placenta grown on cellulose in the presence of wood [28], but they were su⁄cient to undertake a search for ROS that could contribute to cellulose degradation.…”
Section: Cellulose Cleavagementioning
confidence: 68%